Integrated management of fruit trees and Bletilla striata: implications for soil nutrient profiles and microbial community structures - Xie, Qiufeng; Xu, Huimei; Wen, Rouyuan; Wang, Le; Yang, Yan; Zhang, Haizhu; Su, BaoShun (Frontiers in Microbiology, 2024)
In agroforestry ecosystems, forest medicinal compound systems, which involve the cultivation of medicinal plants under the forest canopy, exemplify a unique multi-layered structural approach. This strategy maximizes the utilization of forest resources, including light, temperature, moisture, and soil. It epitomizes a progressive and scientific eco-cultivation method. Nevertheless, there is a conspicuous gap in research related to the shifts in soil nutrients and microbial communities associated with these compound systems. In the present study, we embarked on an examination of the Bletilla striata (C) grown in isolation and in three juxtaposed agroforestry systems based on Bletilla striata (GAB): Apple trees-Bletilla striata (PB), Pear trees-Bletilla striata (LB), and Peach trees-Bletilla striata (TB). We aimed to discern and juxtapose their soil chemical attributes and bacterial assemblages, thereby evaluating the ramifications of agroforestry planting on soil bacterial communities, and the correlation between soil attributes and bacterial communities within the GAB framework. Our findings indicate that compared to soils in the C system, soils under the GAB regimen displayed heightened levels of available nitrogen (AN), available phosphorus (AP), and available potassium (AK). However, they exhibited lower pH values and ammonium nitrogen (NH4 + -N) levels. Notably, when compared to the C system, the TB system revealed a significant elevation in organic matter (OM), the PB system in total phosphorus (TP), and the LB system in total potassium (TK). The bacterial Shannon index under the GAB system displayed a marked increase compared to the C system, while no significant difference was observed in the PB system's Chao1 index. Fungal Shannon indices showed no discernible variation, though the LB system's Chao1 index manifested a significant surge. Based on relative abundance values, GAB soil showed a significant rise in bacterial phyla Myxococcota, Gemmatimonadetes, Acidobacteriota, and fungal phylum Glomeromycota, with a notable decrease in bacterial phylum Proteobacteria and fungal phyla Ascomycota and Chytridiomycota. Moreover, compared to the C system, the PB system displayed a significant increase in bacterial phyla Actinobacteriota and Chloroflexi, and fungal phylum Mucoromycota; the TB system in bacterial phylum Bacteroidota; and the LB system in bacterial phylum Firmicutes and fungal phylum Basidiobolomycota.